EFISIENSI PENGELOLAAN DOKUMEN BERUPA SURAT STUDI KASUS: PT ASTRA INTERNATIONAL TBK - muharani, Anisha; Setyawati, Rosalia Kurni (Jurnal Administrasi dan Kesekretarisan, 2017)
Document in a company is administrative materials which are valuable. Letters cannot be separated from adminstrative activities. Inefficient record management such as false letters clasification, documenting letters and record keepingmanaging letters will hinder the flow of information and administration. There are piles of documents which are priceless but are still recorded or kept. This will of course slow the retrieval of important document. When document is not found easily and quickly, it might be an obstacle of decision making process. Some people stillbelieve that a secretary is responsible for dealing with archives though it not always true. Prompt filing system and files clasification will result in efficiency, and give positive effect for working performance.